The effect of using the (K.W.L.H) strategy on creative thinking and learning some offensive skills in basketball - Shallal, Bashaer R.; Al-Zuhairi, Nibras A.; Al-Dulaimi, Hatem S. (International Journal of Psychosocial Rehabilitation, 2020)
The preparation of educational units using the KWLH strategy)) for freshen and correction skills in basketball for students of the first stage in the College of Physical Education and Sports Science_ Diyala University, and the identify the impact of the KWLH strategy) in creative thinking and learn the skills of class and correction in basketball For students of the first stage. The researchers used the experimental approach to its relevance to the nature of the research. The research sample consisted of (32) students from the first stage distributed on two groups for each group (16 students), and equivalence was found by scale and skill tests. After using a set of statistical means, it was presented and discussed, and the researchers concluded that the educational units prepared using the strategy (K-W-L-H) and the method used in the college had a clear impact on the variables under study, in addition to the superiority of the experimental group over the control in all study variables. In light of the findings, the researchers recommend the adoption of the strategy (K-W-L-H) in the variables under study, as well as a number of similar studies on other sports games.